Empowering the Planet: The 2025 Earth Day Resolution - Dolly Priatna; Kathryn A. Monk; Shujaul Mulk Khan (Universitas Pakuan, 2025)
Earth is the only known planet that supports life, including humanity. Despite seeing ourselves as the most intelligent species in our world, human activities are accelerating the Earth toward irreversible environmental degradation. The consumption of fossil fuels to satisfy our growing demands has led to unprecedented greenhouse gas emissions, pushing the planet toward a potential sixth mass extinction. The rapid rise in carbon dioxide and global temperatures threatens the survival of numerous species, including humanity. Without urgent, collective action to reduce emissions and implement adaptation and mitigation strategies, Earth's ecosystems face catastrophic disruption. Every year on April 22, over one billion people celebrate Earth Day to raise awareness and renew our commitment to protecting our planet. In 2025, under the theme